The existence of liquidity, profitability, and leverage in accounting conservatism - Kurniawan, Cathrien Florencia; Mulyani, Mulyani (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2023)
This study examines the impact of liquidity, profitability, and leverage on accounting conservatism in trading, service, and investment companies listed on the IDX from 2017 to 2019. Financial statements are crucial in depicting an entity's financial performance and aiding decision-making. Accounting conservatism, a principle aimed at mitigating optimistic management behavior, involves recognizing expenses promptly while delaying revenue and asset recognition. Based on a sample of 265 companies, the research utilizes descriptive statistical analysis, pooling tests, and multiple linear regression analysis. The findings indicate that the data is suitable for the study. Hypothesis testing reveals a positive effect of profitability on accounting conservatism, rejecting the first hypothesis. In contrast, the second and third hypotheses are accepted, relating to the negative impact of leverage on accounting conservatism and the inconclusive effect of liquidity. This study contributes to understanding the dynamics of accounting conservatism in the context of diverse company types and market conditions.